Krillfänge im atlantischen Sektor der Antarktis im Südsommer 1977/78 - Nast, F. (1979)
Johann Heinrich von Thunen-Institute, Federal Research Institute for Rural Areas, Forestry and Fisheries began publishing the Informationen aus der Fischereiforschung – Information on Fishery research in 2010